Kollektivtrafik i större städer -En jämförelse av stadstrafiken i Norrköping och Helsingborg - Helal,Zahra (2019)
Public transport is an important part of transport in all cities in Sweden. Travelling sustainably is a way of contributing to a sustainable environment. Therefore many investments have been made to make public transport available and more effective. The purpose of this study is to investigate whether the supply is a key factor to success of public transport in a city compared with another city with similar population. In this study public transport in two cities are compared over time and examined in order to see whether the supply affects the urban travel development in each city. The range includes the frequency and route network coverage for the lines studied. The study focuses on a city that has shown a high increase in public transport, Helsingborg, and a city that has shown a low increase in public transport, Norrköping. City bus lines in both cities and trams in Norrköping have been studied in this report. The method is based on examination of the frequency, the line networks and statistics from both cities. The literature study is based on previous studies of city traffic. Some explanatory parameters that can affect travel are presented in this section. The situation in Helsingborg and Norrköping is described more in detail and thus the two cities' population statistics are compared. The result of the study showed that the supply was a factor that partly affects public transport in both cities. The bus lines in Helsingborg showed a higher frequency in comparison with the bus lines in Norrköping. Thus the frequency of the trams was higher than the frequency of the bus lines in Norrköping. The line network coverage proved to be better in Norrköping's urban area than in Helsingborg's, and the nearness to a bus stop proved to be better in Norrköping. It can therefore be concluded that there was no connection between high public transport and good line network coverage.
Keywords: Nyckelord: Kollektivtrafik i staden; förklaringsvariabler; utbud; turtäthet; linjenät; Helsingborg; Norrköping